Genotype-phenotype correlations of germline mutations in exon 10 of the RET proto-oncogene from 14 MEN2A families of Ethnic Han Chinese - Feng Li; Weiying Chen; Zhenyu Chen; Bijun Lian; Xudong Fang; Hangyang Jin; Huihong Wang; Jianqiang Zhao; Yiming Zhang; Xiaoping Qi (PLoS ONE, 2025)
Objective To investigate the genotype-phenotype correlations of multiple endocrine neoplasia type 2A (MEN2A) caused by mutations in exon 10 of the RET gene in Ethnic Han Chinese. Methods A retrospective analysis was conducted on the family history and genetic characteristics of 14 independent MEN2A pedigrees, all carrying exon 10 mutations of the RET gene, from July 2003 to August 2023. Results A total of 74 out of 133 participants carried germline mutations in exon 10 of the RET gene. The cohort included 26 males and 48 females, with nine types of mutations observed: p.C609R, p.C611F/Y, p.C618G/R/S/Y and p.C620R/S. Of these, the C618 mutation was the most prevalent (71.6%), followed by p.C611 (22.9%), p.C620 (4.1%), and p.C609 (1.4%). The penetrance rates for medullary thyroid carcinoma (MTC), pheochromocytoma, hyperparathyroidism, hirschsprung disease, and cutaneous lichen amyloidosis were 90.3%, 6.9%, 2.8%, 1.4% and 1.4%, respectively. Among the 72 patients with available clinical information, 41 (56.9%) exhibited symptoms of MTC. Comparison of the age at diagnosis, size of MTC, and the positive rate of cervical lymph node metastasis (N1) revealed significant differences between patients with symptomatic and asymptomatic MTC (all P < 0.05). There was a significant difference in the positivity rate of N1 between patients with the p.C618/C620 mutations and those with the p.C609/C611 mutations. Additionally, there was a significant difference in the initial serum calcitonin levels between N1 and N0 patients (P < 0.05). Conclusion Exon 10 mutations of the RET gene are frequently located in codon 618 and contribute to the familial MTC phenotype. To improve the recognition of MEN2A, integrating family history, testing for RET mutations, and monitoring serum calcitonin levels are essential for early diagnosis and personalised treatment.